Spectral functions and negative density of states of a driven-dissipative nonlinear quantum resonator - Scarlatella, O; Clerk, A; Schiro, M (IOP Publishing, 2019)
We study the spectral properties of Markovian driven-dissipative quantum systems, focusing on the nonlinear quantum van der Pol oscillator as a paradigmatic example. We discuss a generalized Lehmann representation, in which single-particle Green's functions are expressed in terms of the eigenstates and eigenvalues of the Liouvillian. Applying it to the quantum van der Pol oscillator, we find a wealth of phenomena that are not apparent in the steady-state density matrix alone. Unlike the steady state, the photonic spectral function has a strong dependence on interaction strength. Further, we find that the interplay of interaction and non-equilibrium effects can result in a surprising 'negative density of states', associated with a negative temperature, even in absence of steady state population inversion.